Lack of compliance: a challenge for digital dermoscopy follow-up - Guilherme Augusto Gadens (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND: Digital dermoscopy is the gold standard follow-up method for patients with high risk for developing cutaneous malignant melanoma. By comparing the same lesion at different moments, it allows early detection of subtle changes that could suggest the diagnosis of melanoma. Thus, it is clear that the test must be repeated after a period of time, according to time intervals determined by the evaluator. OBJECTIVES: To evaluate adherence of patients to follow-up examinations using digital dermoscopy. METHOD: Retrospective analysis of 36 patients who underwent digital dermoscopic examination and total-body photography in a private medical center between September 2010 and January 2013. Results: Only 25% of the patients returned for followup evaluations. CONCLUSIONS: Low adherence to digital dermoscopy follow-up could compromise the efficacy of this valuable method. This lack of adherence represents a challenge for the evaluator.